Time to pregnancy recognition among users of an FDA-cleared fertility application - Agathe van Lamsweerde; Jack T. Pearson; Rachel Urrutia; Kristina Gemzell-Danielsson; Helena Kopp Kallner; Anita Nelson; Eleonora Benhar; Carlotta Favaro; Elina Berglund Scherwitzl; Raoul Scherwitzl (Journal of Obstetrics and Gynaecology)
Background Previous investigations of time-to-pregnancy recognition have analysed data from national surveys and clinics, but this has not been investigated in the context of digital fertility applications. Timely pregnancy recognition can help individuals in health and pregnancy management, reducing maternal and foetal risk and costs, whilst increasing treatment options, availability, and cost.Methods This dataset contained 23,728 pregnancies (conceived between June 2018 and December 2022) from 20,429 participants using a Food and Drug Administration (FDA) cleared fertility app in the United States. Most participants (with non-missing information) identified as Non-Hispanic White, and one-third reported obtaining a university degree. We used two-tailed Welch’s t-test, Mann–Whitney U-test, and two-tailed Z-tests to compare time to pregnancy recognition between those using the app to conceive or contracept.Results Participants using an app to conceive recognised pregnancy on average at 31.3 days from last menstrual period (LMP) compared to 35.9 days among those using the app to prevent pregnancy.Conclusion Generalisability is limited, as all participants were using a fertility app and had relatively homogenous sociodemographic characteristics.